Rising energy prices without falling consumption? The role of energy price dispersion in a multi-product world - Kathrine von Graevenitz; Joscha Krug; Elisa Rottner (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Governments around the world are under pressure to reduce industrial energy use and emissions without losing out to international competition. For this reason, climate policies often come with exemptions or additional support for large energyintensive firms, increasing the heterogeneity in energy prices. We document such a rising dispersion in industrial energy prices in the German manufacturing sector that coincides with rising average energy prices. Surprisingly, we observe an increase in industrial energy intensity, while at the same time, manufacturing firms have shifted toward producing less energy intensive products. We develop a model of multi-product firms with heterogeneous energy prices and heterogeneous products that can partially explain this puzzle via a 'reshuffling' among producers: If energy prices rise only for a share of firms, those firms will drop energy-intensive products. But the remaining low energy price firms will increase their market share of these products and produce them in a less energy-efficient way. Empirical analyses based on German administrative firm data suggest that such a 'reshuffling' is indeed taking place. We show in a simple quantification that reshuffling can have sizable effects on aggregate energy intensity.
Keywords: Q41; D21; D22; 330; Product choice; Energy intensity; Carbon emissions; Manufacturing